Platelet-to-Lymphocyte Ratio as a Prognostic Biomarker for Overall Survival in Glioma Patients: A Retrospective Cohort Study in Yogyakarta, Indonesia - Ermawati, Tutik (Fakultas Kedokteran Universitas Jenderal Soedirman, 2025)
Background: Glioma is the most common primary brain tumor in adults, with a generally poor prognosis despite advances in treatment. Inflammation plays a role in tumor initiation, progression, and invasion. The platelet-to-lymphocyte ratio (PLR) is a minimally invasive, cost-effective biomarker that may predict overall survival (OS) in glioma patients. Objective: This Study aims to evaluate the association between pre-treatment PLR and overall survival in patients with glioma. Methods: This retrospective cohort study included glioma patients treated at Dr. Sardjito General Hospital and affiliated hospitals in Yogyakarta between 2017–2022. PLR was calculated from pre-treatment complete blood counts. The optimal cut-off value was determined via ROC curve analysis. Kaplan–Meier survival analysis and Cox proportional hazards regression were performed to evaluate associations between PLR and OS, adjusting for age, sex, tumor grade, size, location, surgery type, and Karnofsky Performance Status (KPS). Results: A total of 149 patients were included (median age: 48 years; 57.7% male; 69.1% high-grade glioma). The optimal PLR cut-off was 236.77 (AUC = 0.591; sensitivity = 42.9%; specificity = 77.8%). Median OS was 14.1 months for PLR < 236.77 versus 5.8 months for PLR ≥ 236.77. High PLR was associated with increased mortality risk (HR = 2.18; 95% CI: 1.37–3.45).nConclusion: Elevated pre-treatment PLR is independently associated with shorter OS in glioma patients. PLR may serve as a simple, inexpensive prognostic biomarker in clinical practice, particularly in resource-limited settings.